1977
DOI: 10.1111/j.1365-2842.1977.tb00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Bruxism and its effect on the teeth

Abstract: This study presents the progress of tooth wear and the change in structural morphology on individual teeth of bruxist subjects, compared with non-bruxers. From the results of this investigation it can be concluded that the tooth wear progressed faster in bruxers than in non-bruxers. Scanning electron microscope investigations revealed in 10 teeth the same pattern of deep grooves and striations on the wear-facets of active bruxers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
1
21

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(90 citation statements)
references
References 13 publications
(9 reference statements)
6
62
1
21
Order By: Relevance
“…Whether or not bruxism causes noncarious cervical lesions is controversial. Many studies showed higher prevalence of NCCLs was in subjects with a bruxing habit than in subjects without a bruxing habit [26]. But other studies revealed that significant relationship between the two wasn't found [15,27].…”
Section: Etiology and Risk Factorsmentioning
confidence: 98%
“…Whether or not bruxism causes noncarious cervical lesions is controversial. Many studies showed higher prevalence of NCCLs was in subjects with a bruxing habit than in subjects without a bruxing habit [26]. But other studies revealed that significant relationship between the two wasn't found [15,27].…”
Section: Etiology and Risk Factorsmentioning
confidence: 98%
“…For example, Xhonga 6) found the prevalence of these lesions to be significantly higher in patients who were bruxists, while Lambrechts et al 7) found that bruxism and malocclusion were associated with abfraction lesions.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…The abfraction is accelerated by excessive occlusal load such as occlusal interferences, premature contacts, bruxism, and clenching habit 10) . Loss of tooth structure in the cervical area of a NCCLs may cause esthetic problems and discomfort due to dentinal hypersensitivity 1,3,6) , but not all lesions require restorations 11) . The decision to restore NCCLs is based on the desire to strengthen the tooth and decrease the theoretical stress concentration and flexure, mitigate lesion progression, prevent hypersensitivity and pulp involvement, improve oral hygiene and enhance esthetics 11,12) .…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…Tooth wear is not caused by trauma and bacteria [2,3]. The etiological factors include consumption of acidic drinks and foods, bruxism, nail biting, wrong tooth brushing technique, types of dentifrice and using toothbrush with hard bristle [4,5,6,7]. A few studies reported that the prevalence is increasing due to the increasing population's age [8,9,10].…”
Section: Introductionmentioning
confidence: 99%